The Role of Tangibility, Business Risk, and Managerial Ownership on Capital Structure - Febryanti Simon; Sistya Rachmawati; Etty Murwarningsari (AIBPM Publisher, 2025)
A poll performed by the “Ministry of Manpower of the Republic of Indonesia” revealed that a significant majority of enterprises, specifically 88%, saw financial disruption during the Covid-19 outbreak. Efficient management of capital structure is essential for firms to withstand periods of crisis. The aim of this study is to analyze the elements that can impact the formation of a company's capital structure. “The population for this study consists of all companies that are listed on the IDX (Indonesia Stock Exchange) from 2020 to 2022”. This study utilized purposive sampling to choose the sample. The study utilizes secondary data acquired from financial statements accessible from the website www.idx.co.id. This study uses multiple regression analysis utilizing EViews 12 software to analyze the data. The hypothesis Ha1 is confirmed, suggesting that business risk has ab statistically significant adverse effect on capital structure, as indicated by a p-value of 0.03 (0.05). Ha3 is valid, the presence of tangible assets can amplify the influence of business risk on the capital structure. This study indicates that companies can efficiently control the allocation of external and internal funds by considering business risks and managerial ownership